2012
DOI: 10.1016/j.jval.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Effectiveness Evaluation of Prophylactic HPV Vaccine in Developing Countries

Abstract: Compared with commonly accepted standard thresholds recommended by the World Health Organization Commission on Macroeconomics and Health, the nationwide coverage of HPV vaccination in girls is likely to be cost-effective in Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 38 publications
4
52
0
Order By: Relevance
“…This local threshold is below the thresholds put forward by the WHO and has been used as a reference value in some vaccine evaluations for Thailand [13]. However, other studies evaluating HPV and rotavirus vaccination in Thailand have used the 'WHO-CHOICE thresholds' instead of the local threshold [14][15][16]. Again, these studies have often made a distinction between interventions that represent value for money (i.e.…”
Section: How Have the Who-choice Thresholds Been Used For Vaccines Inmentioning
confidence: 99%
“…This local threshold is below the thresholds put forward by the WHO and has been used as a reference value in some vaccine evaluations for Thailand [13]. However, other studies evaluating HPV and rotavirus vaccination in Thailand have used the 'WHO-CHOICE thresholds' instead of the local threshold [14][15][16]. Again, these studies have often made a distinction between interventions that represent value for money (i.e.…”
Section: How Have the Who-choice Thresholds Been Used For Vaccines Inmentioning
confidence: 99%
“…Recent studies on the use and efficacy of the HPV vaccine in developing countries have suggested that vaccine distribution could be an effective way to mitigate cervical cancer in low-and middle-income countries (Fesenfeld et al, 2013;Termrungruanglert et al, 2012). Demonstration projects in Peru, India, Uganda, and Vietnam have shown high levels of vaccination coverage using schoolbased programs targeting teen girls (LaMontagne et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…With the goal to increase the HPV vaccination in mind, it is essential to set up HPV vaccination interventions which are well tailored for the young female population. Lastly, while the financial cost has been the major prohibitive factor to add the vaccine on the national vaccination program [31], more evidence has shown that the vaccine is cost effective compared to the cost of HPV and anogenital cancer treatments and damage to the quality of life [32,33]. In Thailand, the series of HPV vaccines cost between US$ 180 and US$ 340, while the gross national income per capita was approximately US$ 3,900 [33].…”
mentioning
confidence: 99%